ANALISA TINGKAT PENERIMAAN PELANGGAN SELULAR TERHADAP LAYANAN SELULAR BERBASIS 3G PADA PELAJAR SMP DI KABUPATEN TANGERANG - Triyono Triyono (Jurnal Teknik, 2016)
Thepurposeofthisresearchwastodeterminefactorsinfluencingacceptancelevelof3GonmobilephonescustomersinKabupaten Tangerang. There arefive constructs compiled into a structuralmodeltoexplain customer acceptancelevelof3G, i.e. perceivedusefulness,perceivedease ofuse,perceivedenjoyment,attitude towards using,andbehavioralintention.Theresearchsubjectisjuniorhighschoolstudents thatusedmobilephones inKabupatenTangerang.Theprocessofdatacollectionused simplerandomsampling methodbyrandomlytakingalljuniorhighschoolstudents. Themethoddataanalysisusedinthisresearchis usingtheregression.Theresulstof thisresearchindicatethatmodelofTAMcanexplainfactorsinfluencingacceptance of usageof 3G. Theresults showed thatthe overallproposed hypothesis was accepted. Keywords: mobilephones, 3G, Technology Acceptance Model, students